La Narrativa venezolana de la época del Modernismo - Silva Beauregard, Paulette (Revista Chilena de Literatura, 2016)
La autora se propone abordar en un grupo representativo de novelas venezolanas de las últimas décadas del s. XIX y primeros años de este siglo, el problema de la función del hombre de letras en la sociedad y cómo reflexiona sobre este tema el discurso de la novela venezolana, tanto de narrador como de personajes. Este problema es típicamente modernista, y la novela de este período sirvió como un espacio adecuado para el examen de él y de la necesidad de una acción posterior consecuente, tanto dentro como fuera de la novela. The author proposes to approach the problem of the man of letters' function in society and how the course of the Venezuelan novel reflects this subject, in the novel of narrator as well as characters, in a representative group of Venezuelan novels from the final decades of the 19th century and the first years of this century. This problem is a typically modern one, and the novel from this period provided adequate space for its examination and for the need for consequent later action, within as well as outside of the novel.